The spirit glass - Chokshi, Roshani (Disney, Hyperion, 2023)
"Corazon yearns to finally start training as a babaylan (a mystical healer and spirit guide) under her powerful guardian, Aunt Tina. As soon as her magic awakens, Corazon plans to bring her parents back from the dead and no longer have to rely on a soul key to allow visits with their ghosts for a few hours every Saturday night. But when a vengeful ghost steals Corazon's precious key, the fragile balance between the human world and the spirit world is thrown out of whack. Aunt Tina reveals that if Corazon wants her magic to awaken, then she must lay the ghost to rest by fashioning a new soul key. With her rather bloodthirsty gecko companion, Saso, Corazon embarks on a quest through the spirit realms. But they must move quickly, for if the ghost gets through the spirit glass, all hope will be lost. Roshani Chokshi pays tribute to her Filipino heritage in this book that has all the magic, sparkle, and heart that made her Aru Shah series a fantasy classic" --